2012
DOI: 10.3389/fneur.2012.00041
|View full text |Cite
|
Sign up to set email alerts
|

REM Sleep Rebound as an Adaptive Response to Stressful Situations

Abstract: Stress and sleep are related to each other in a bidirectional way. If on one hand poor or inadequate sleep exacerbates emotional, behavioral, and stress-related responses, on the other hand acute stress induces sleep rebound, most likely as a way to cope with the adverse stimuli. Chronic, as opposed to acute, stress impairs sleep and has been claimed to be one of the triggering factors of emotional-related sleep disorders, such as insomnia, depressive- and anxiety-disorders. These outcomes are dependent on ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 169 publications
3
58
0
Order By: Relevance
“…An increased arousal threshold to the alarm is likely to indicate an accumulation of sleep debt (Bruck, 1995). An increased arousal threshold is also consistent with research showing an increased need for sleep following exposure to stress (Sucheki et al, 2012). Paradoxically, high levels of pre-sleep stress have also been associated with difficulty initiating sleep (Wuyts et al, 2012).…”
Section: Discussionmentioning
confidence: 60%
“…An increased arousal threshold to the alarm is likely to indicate an accumulation of sleep debt (Bruck, 1995). An increased arousal threshold is also consistent with research showing an increased need for sleep following exposure to stress (Sucheki et al, 2012). Paradoxically, high levels of pre-sleep stress have also been associated with difficulty initiating sleep (Wuyts et al, 2012).…”
Section: Discussionmentioning
confidence: 60%
“…Among these, CRH and cortisol produced by the HPA axis, and melatonin secreted by the pineal are most related to biological rhythms and sleep: CRH inhibits slow-wave sleep and triggers the sleep-wake transition; reduced CRH synthesis or CRH receptor blockade increases the duration of non-rapid eye movement (NREM) sleep and suppresses arousal [82] . Moreover, high concentrations of cortisol have effects similar to CRH, which include inhibiting NREM and prolonging arousal time.…”
Section: The Circadian Rhythm Disorder Hypothesis and New Targets Formentioning
confidence: 99%
“…Moreover, high concentrations of cortisol have effects similar to CRH, which include inhibiting NREM and prolonging arousal time. Meanwhile, it also reduces the latency of rapid eye movement (REM) sleep and increases the sleep density in REM sleep [82] . In contrast, melatonin has the opposite effects; it not only shortens the time to fall asleep and improves sleep quality, but also directly regulates the biological rhythms in the suprachiasmatic nucleus, especially the sleep-wake rhythm, through a melatonin receptor-GABA mechanism, thereby improving sleep rhythm disorders and endocrine disorders.…”
Section: The Circadian Rhythm Disorder Hypothesis and New Targets Formentioning
confidence: 99%
“…There was a non-significant (p = .051) difference in REM sleep, with participants obtaining 8 min more REM on the on-call night. Recent research has suggested that increases in REM sleep forms part of an adaptive response assisting in recovery from stressful situations, for example car accidents or other traumatic events [25]. Therefore, one possible reason for this result is that, knowing they were going to be woken by loud call overnight participants' stress levels increased, which, in turn, interfered with their REM sleep.…”
Section: Discussionmentioning
confidence: 85%